Evidence for the role of AMPK in regulating PGC‐1 alpha expression and mitochondrial proteins in mouse epididymal adipose tissue. (20th September 2013) - Wan, Zhongxiao; Root‐Mccaig, Jared; Castellani, Laura; Kemp, Bruce E.; Steinberg, Gregory R.; Wright, David C.
<x xml:space="preserve">Abstract</x> Objective PGC‐1α is a transcriptional co‐activator and master regulator of mitochondrial biogenesis. While extensively studied in skeletal and cardiac muscle, recent findings suggest that white adipose tissue PGC‐1α plays an important role in regulating glucose homeostasis. The purpose of the present investigation was to evaluate the role of AMPK in regulating PGC‐1α and mitochondrial enzymes in mouse epididymal and inguinal subcutaneous adipose tissue. Methods Mitochondrial protein content and norepinephrine and CL 316, 243‐induced PGC‐1α mRNA expression were studied in mouse epididymal and inguinal adipose tissue from wild‐type and AMPK β1−/− mice. Results The protein content and phosphorylation of AMPKα was reduced in epididymal adipose tissue from AMPK β1−/− compared to WT mice, concomitant with decreases in PGC‐1α and mitochondrial marker proteins. Norepinephrine and CL 316, 243‐mediated induction of PGC‐1α were decreased in cultured epididymal adipose tissue from AMPK β1−/− relative to WT mice. In inguinal adipose tissue from AMPK β1−/− mice, mitochondrial marker protein content and norepinephrine and CL 316, 243‐mediated increases in PGC‐1α were normal despite reductions in the content and phosphorylation of AMPKα. Conclusions Norepinephrine‐ and CL 316, 243‐mediated induction of PGC‐1α and mitochondrial protein expression is regulated by AMPK in epididymal, but not inguinal adipose tissue.